Carbon Emissions, Health Expenditure, and Economic Effects on Life Expectancy in Malaysia - Norkhairunnisa Redzwan; Rozita Ramli (World)
Population aging, urbanization, and life expectancy are among the main pillars of sustainable economic, social, and environmental development of the future, as outlined by the Sustainable Development Goals (SDGs) of the United Nations. Globally, the current population structure exhibits an increasing proportion of the elderly along with rising healthcare costs and climate change. Malaysia faces a similar experience, where 14% of its population is expected to account for the elderly by 2030. To achieve the SDGs, attention should be given to their pillars, namely life expectancy, health expenditure, economic development, and carbon emissions. Limited research that addresses these key factors has been conducted, especially in emerging economies, such as Malaysia. Therefore, this study aims to contribute to the existing literature by analyzing the long-term and short-term relationships between carbon emissions, GDP, health expenditure, and life expectancy in Malaysia. The autoregressive distributed lag (ARDL) bounds cointegration test was adopted to determine the long-term and short-term effects on life expectancy from 1997 to 2021. The findings indicate that cointegration existed among the variables, and carbon emissions and health expenditure had a statistically significant relationship with life expectancy in the short run. Hence, greater attention should be paid to these two factors, particularly in the short term, to ensure that Malaysia can maintain the health and well-being of the nation in line with the SDG requirements.